Pharmacological Inhibition of MALT1 Protease Leads to a Progressive IPEX-Like Pathology - Martin, Kea; Junker, Ursula; Tritto, Elaine; Sutter, Esther; Rubic-Schneider, Tina; Morgan, Hannah; Niwa, Satoru; Li, Jianping; Schlapbach, Achim; Walker, Dana; Bigaud, Marc; Beerli, Christian; et al. (Frontiers in Immunology, 2020)
Genetic disruption or short-term pharmacological inhibition of MALT1 protease is effective in several preclinical models of autoimmunity and B cell malignancies. Despite these protective effects, the severe reduction in regulatory T cells (Tregs) and the associated IPEX-like pathology occurring upon congenital disruption of the MALT1 protease in mice has raised concerns about the long-term safety of MALT1 inhibition. Here we describe the results of a series of toxicology studies in rat and dog species using MLT-943, a novel potent and selective MALT1 protease inhibitor. While MLT-943 effectively prevented T cell-dependent B cell immune responses and reduced joint inflammation in the collagen-induced arthritis rat pharmacology model, in both preclinical species, pharmacological inhibition of MALT1 was associated with a rapid and dose-dependent reduction in Tregs and resulted in the progressive appearance of immune abnormalities and clinical signs of an IPEX-like pathology. At the 13-week time point, rats displayed severe intestinal inflammation associated with mast cell activation, high serum IgE levels, systemic T cell activation and mononuclear cell infiltration in multiple tissues. Importantly, using thymectomized rats we demonstrated that MALT1 protease inhibition affects peripheral Treg frequency independently of effects on thymic Treg output and development. Our data confirm the therapeutic potential of MALT1 protease inhibitors but highlight the safety risks and challenges to consider before potential application of such inhibitors into the clinic.